Influence of Secondary Hyperparathyroidism Induced by Low Dietary Calcium, Vitamin D Deficiency, and Renal Failure on Circulating Rat PTH Molecular Forms - Pierre D'Amour; Louise Rousseau; Stephen Hornyak; Zan Yang; Tom Cantor (International Journal of Endocrinology)
Rats(r) with secondary hyperparathyroidism were studied to define the relationship between vitamin D metabolites and rPTH levels measured by 3 different rat ELISAs. Controls and renal failure (RF) rats were on a normal diet, while 2 groups on a low-calcium (-Ca) or a vitamin D-deficient (-D) diet. RF was induced surgically. Mild RF rats had normal calcium and 25(OH)D but reduced 1,25(OH)2D levels (P<.001) with a 2.5-fold increased in rPTH (P<.001). Severe RF rats and those on a -Ca or -D diet had reduced calcium (P<.01) and 25(OH)D levels (P<.05), with rPTH increased by 2 (-Ca diet; P<.05), 4 (-D diet; P<.001), and 20-folds (RF; P<.001) while 1,25(OH)2D was high (-Ca diet: P<.001) or low (-D diet, RF: P<.001). 25(OH)D and 1,25(OH)2D were positively and negatively related on the -Ca and -D diets, respectively. rPTH molecular forms behaved as expected in RF and on -Ca diet, but not on -D diet with more C-rPTH fragments when less were expected. This may be related to the short-time course of this study compared to prior studies.